Apocynin protects retina cells from ultraviolet radiation damage via inducing sirtuin 1. (15th March 2020) - Liu, Feng; Lin, Chen; Hong, Jinsheng; Cai, Chuanshu; Zhang, Weijian; Zhang, Jianrong; Guo, Lihong
Abstract: Direct exposure to Ultraviolet (UV) radiation causes progressive damages in retinal cells, which is one of the hypothetical mechanisms underlying age-related retinopathy or macular degeneration. The protective effects of Apocynin against UV damages were firstly tested in retinal pigment epithelium cells (RPEs) and retinal ganglion cells (RGCs). Subsequently the beneficial effect of Apocynin on mouse retinas against light damage were examined. Next, microarray profiling was used to identify the genes regulated by Apocynin in both RPEs and RGCs. A candidate gene was isolated for functional characterisation by knock-down study. Apocynin was shown to inhibit cell death, reduce oxidative stress and deoxyribonucleic acid damages in both RPEs and RGCs challenged with UV. Intravitreal application of Apocynin also improved retinal dysfunction caused by light damage. Sirtuin 1 (SIRT1) was identified as induced by Apocynin by microarray study. The induction was confirmed by realtime-PCR and western blotting. Knocking down SIRT1 antagonised the protective effect of Apocynin against UV damages in both RPEs and RGCs. Apocynin is a novel agent that shows both in vitro and in vivo efficacies against UV radiation induced retina damages. SIRT1 pathway is implicated in UV radiation protection of Apocynin in retinal cells.